Skin exposure to soil microbiota elicits changes in cell-mediated immunity to pneumococcal vaccine - Roslund, Marja I; Nurminen, Noora; Oikarinen, Sami; Puhakka, Riikka; Grönroos, Mira; Puustinen, Leena; Kummola, Laura; Parajuli, Anirudra; Cinek, Ondřej; Laitinen, Olli H; Hyöty, Heikki; Sinkkonen, Aki (Scientific reports, 2024)
A resilient immune system is characterized by its capacity to respond appropriately to challenges, such as infections, and it is crucial in vaccine response. Here we report a paired randomized intervention-control trial in which we evaluated the effect of microbially rich soil on immune resilience and pneumococcal vaccine response. Twenty-five age and sex matched pairs of volunteers were randomized to intervention and control groups. The intervention group rubbed hands three times a day in microbially rich soil until participants received a pneumococcal vaccine on day 14. Vaccine response, skin and gut bacteriome and blood cytokine levels were analyzed on days 0, 14 and 35. Peripheral blood mononuclear cells (PBMCs) were stimulated with vaccine components and autoclaved soil for cytokine production. Commensal bacterial community shifted only in the intervention group during the 14-day intervention period. When PBMCs collected on day 14 before the vaccination were stimulated with the vaccine components, IFN-y production increased in the intervention but not in the control group. On day 35, vaccination induced a robust antibody response in both groups. In parallel, gut bacterial community was associated with TGF-β plasma levels and TGF-β decrease in plasma was lower in the intervention group. The results indicate that exposure to microbially rich soil can modulate the cell-mediated immunity to components in pneumococcal vaccine.
Keywords: Gastrointestinal Microbiome; vakcinace; Humans; pneumokokové infekce; Immunity, Cellular; lidé středního věku; Vaccination; mikrobiota; cytokiny; Female; kůže; dospělí; Leukocytes, Mononuclear; Microbiota; lidé; Pneumococcal Infections; pneumokokové vakcíny; buněčná imunita; Adult; ženské pohlaví; Pneumococcal Vaccines; Male; Middle Aged; půdní mikrobiologie; Cytokines; leukocyty mononukleární; střevní mikroflóra; mužské pohlaví; Skin; Soil Microbiology